Trends in bottlenose dolphin (Tursiops truncatus) strandings in South Carolina, USA, 1997-2003: implications for the Southern North Carolina and South Carolina Management Units - McFee, Wayne E.; Hopkins-Murphy , Sally R. (J. Cetacean Res. Manage., 2023)
Trends in marine mammal stranding rates over multiple years can provide useful information on life history parameters, seasonal and spatial distribution and both natural and human-induced mortality rates when compared with baseline data. Data of bottlenose dolphin (Tursiops truncatus) stranding rates in South Carolina, USA from 1997-2003 were analysed. The objectives of this study were to: (1) compare recent trends in strandings with baseline data (1992-1996) for South Carolina; (2) compare strandings between the Southern North Carolina Management Unit (SNCMU) and the South Carolina Management Unit (SCMU); (3) determine annual, seasonal and spatial trends in bottlenose dolphin strandings; (4) investigate seasonal reproductive trends; and (5) determine the extent to which humans may affect stranding rates (human interactions). Bottlenose dolphins stranded in South Carolina are assumed to be from at least two of the seven management units recognised by the National Marine Fisheries Service in the Western North Atlantic: the SNCMU and the SCMU. During the study period, 302 bottlenose dolphin strandings were reported in South Carolina and stranding counts were analysed using a Generalised Linear Model. Results showed that there were significantly more bottlenose dolphin strandings in the spring and autumn as compared with summer and winter. The effect of season was highly significant for the number of neonate strandings, suggesting a bimodal reproductive cycle in spring and autumn for the study area. A significant increase in the number of strandings of all age classes was found in the autumn for the northern portion of the State (SNCMU), supporting the assumption that bottlenose dolphins from the north migrate into South Carolina waters during this time of year. Rope entanglements was the most common source of human interaction, with the crab pot fishery the most prevalent source of fishery mortality in South Carolina. This study demonstrates the usefulness of a long-term stranding database by increasing knowledge of temporal and spatial patterns and for monitoring neonate and human-induced mortality.